Biocontrol Effect and Antibacterial Mechanism of Bacillus velezensis TRMB57782 Against Alternaria gaisen Blotch in Korla Pears - Chaowen Liu; Tiancai Wang; Yuxin Zhang; Hui Jiang; Xiaoxia Luo (Biology, 2025)
Pear black spot disease seriously threatens the pear industry. Currently, its control mainly relies on chemical fungicides while biological control using antagonistic microorganisms represents a promising alternative approach. This study identified and characterized Bacillus velezensis TRMB57782 as a biocontrol strain through whole-genome sequencing. AntiSMASH analysis predicted the strain’s potential to produce secondary metabolites such as surfactin, difficidin, and bacilysin. In vitro experiments demonstrated that TRMB57782 inhibited the growth of Alternaria gaisen. In vivo experiments using excised branches and pear fruits at two different stages also showed significant control effects. A preliminary exploration of the metabolic substances of TRMB57782 was carried out. The strain can produce siderophores and three biocontrol enzymes. Crude extracts obtained by the hydrochloric acid precipitation and ammonium sulfate saturation precipitation of the bacterial liquid exhibited significant activity and volatile organic compounds showed biocontrol activity. Meanwhile, the effects of strain TRMB57782 on the hyphae of pathogenic fungi were studied, leading to hyphal atrophy and spore shrinkage. This paper provides an effective biocontrol strategy for fragrant pear black spot disease, reveals the antibacterial mechanism of Bacillus velezensis TRMB57782, and offers a new option for the green control of pear black spot disease.